ALMA–IRDC – II. First high-angular resolution measurements of the 14N/15N ratio in a large sample of infrared-dark cloud cores. Issue 3 (22nd March 2021) - Fontani, F; Barnes, A T; Caselli, P; Henshaw, J D; Cosentino, G; Jiménez-Serra, I; Tan, J C; Pineda, J E; Law, C Y
ABSTRACT: The 14 N/ 15 N ratio in molecules exhibits a large variation in star-forming regions, especially when measured from N2 H + isotopologues. However, there are only a few studies performed at high-angular resolution. We present the first interferometric survey of the 14 N/ 15 N ratio in N2 H + obtained with Atacama Large Millimeter Array observations towards four infrared-dark clouds harbouring 3 mm continuum cores associated with different physical properties. We detect N 15 NH + (1–0) in $\sim 20\!-\!40{{\ \rm per\ cent}}$ of the cores, depending on the host cloud. The 14 N/ 15 N values measured towards the millimetre continuum cores range from a minimum of ∼80 up to a maximum of ∼400. The spread of values is narrower than that found in any previous single-dish survey of high-mass star-forming regions and than that obtained using the total power data only. This suggests that the 14 N/ 15 N ratio is on average higher in the diffuse gaseous envelope of the cores and stresses the need for high-angular resolution maps to measure correctly the 14 N/ 15 N ratio in dense cores embedded in IRDCs. The average 14 N/ 15 N ratio of ∼210 is also lower than the interstellar value at the Galactocentric distance of the clouds (∼300–330), although the sensitivity of our observations does not allow us to unveil 14 N/ 15 N ratios higher than ∼400. No clear trend is found between the 14 N/ 15 N ratio and the core physical properties. We find only a tentative positive trend between 14 N/ 15 N and H2 column density. However, firmer conclusions can be drawn only with higher sensitivity measurements.